The Legal Protection for Notaries against Making of Deeds Based on Document Following by Acceptors - Nur Afifah F., Novy Dika (Jurnal Konstatering, 2022)
Notaries, within their limitations, often cannot anticipate the parties who want to deliberately take actions that are prohibited by the rule of law. The notary is not an investigator of the deeds he makes, but is only limited to making authentic deeds against the wishes of the parties in his position as a public official.. This research aims toknow and analyze about Legal Protection for Notaries against Making Deeds Based on Forgery of Documents by Appearers. (Study of the Decision of the Supreme Court of the Republic of Indonesia Number: 385 K/PID/2006), and to find out and analyze the Legal Position of Deeds made by Notaries Based on Fake Documents by Appearers. The approach method in this study is the normative juridical approach. The specification of this study uses descriptive analysis specifications. The data required includes primary data, which consists of the 1945 Constitution; Act No. 2 of 2014; Criminal Code; The Criminal Procedure Code; Code of Civil law; Notary Code of Ethics, as well as secondary and tertiary data containing books and other supporting documents. Taken by the method of data collection by way of library research (Library Research). Methods of data analysis using qualitative methods. Based on the research concluded Legal protection for Notariesin the Case of the Decision of the Supreme Court of the Republic of Indonesia Number 385 K/Pid/2006 the Judge stated that the Defendant's actions were proven but not a criminal act, so that the Defendant was released from all lawsuits and that in the a quo case, the Defendant as a Notary was not authorized to examine whether or not the Underhand Power of Attorney submitted by the Appellant. The legal status of a deed made by a Notary based on fake documents is null and void.Keywords: Documents; Fake; Notary; Protection; Public.